Dietary acid load berhubungan dengan sindrom metabolik dan kesehatan mental pada mahasiswi obesitas - Firdananda Fikri Jauharany; Martha Irene Kartasurya; Apoina Kartini; Fillah Fithra Dieny; Dian Ratna Sawitri; Etika Ratna Noer (Jurnal Gizi Klinik Indonesia, 2021)
The dietary acid load was associated with metabolic syndrome and mental health among obese college studentsBackground: The prevalence of metabolic syndrome has been increasing every year in the young population. The western diet is one of the causes that makes excess acid in the body called a dietary acid load. On the other hand, the high dietary acid load was associated with decreased mental health status.Objective: To examine the association between dietary acid load and the risk of metabolic syndrome and mental health.Methods: This was a cross-sectional study conducted with 115 female students in Semarang aged 18-22 years. The dietary acid load was evaluated through a potential renal acid load (PRAL), the risk score for metabolic syndrome was calculated by Metabolic syndrome risk score. Mental health status was assessed through levels of self-esteem and levels of anxiety. The level of self-esteem was measured by the Rosenberg Self-Esteem Scale questionnaire, while the level of anxiety was measured by the State Anxiety Inventory questionnaire. Multiple linear regression models with adjustment for a potential cofounding variable were used to evaluate the association between dietary acid load with metabolic syndrome scores, self-esteem scores, and anxiety scores.Results: The mean PRAL score was 6.11 ± 9.72 mEq/day indicated the intake of the subjects was the dietary acid load. 13% of subjects had metabolic syndrome, and 87% had a pre-metabolic syndrome. 36.5% of the subjects have low self-esteem scores. The anxiety level score calculation shows that 59.1% of the subjects are at high risk of anxiety. Pearson test showed that PRAL scores were correlated with anxiety scores (r=0,669; p<0,001). The linear regression test showed that PRAL scores were correlated with metabolic syndrome scores (β=0.899; p<0.001) and self-esteem scores (β =-0.069; p=0.047).Conclusions: High dietary acid load may be a risk factor related to the development of metabolic disorders and decreased mental health status in females with obesity.